Enhancing the energetic efficiency of MDEA/PZ-based CO2 capture technology for a 650 MW power plant: Process improvement. (1st January 2017) - Zhao, Bin; Liu, Fangzheng; Cui, Zheng; Liu, Changjun; Yue, Hairong; Tang, Siyang; Liu, Yingying; Lu, Houfang; Liang, Bin
Highlights: MDEA/PZ solutions are more energetically efficient for post-combustion CO2 capture. Various process improvements effectively enhance the process energy efficiency. A reboiler heat duty ( Q reb ) of 2.24 G J/t CO2 was achieved. The net power efficiency penalty was reduced from 9.13% to 7.66%. Abstract: Post-combustion CO2 capture (PCC) facilities are set up at the power plants to reduce their carbon footprint. However, the high energy demand of the amine-based PCC technologies significantly decreases the net energy efficiency of a power plant. This work focused on developing an optimal amine-based PCC technology by carefully analyzing and integrating the energy flow. The methyldiethanolamine (MDEA) solution of lower reaction heat with CO2 is found to be a superior solvent than monoethanolamine (MEA). Process analysis using the equilibrium stage model in Aspen Plus was performed to investigate the effects of piperazine (PZ) promoter and various operation parameters such as absorption pressure, stripping pressure, CO2 loading in lean solution, and CO2 removal ratio on the net efficiency penalty of MDEA/PZ-based PCC process. Several enhancement measures, including the absorber intercooling, simple rich-split, advanced rich-split, and stripper interheating, were found significantly improving the process energetic efficiency. A reboiler heat duty ( Q reb ) as low as 2.24 G J/t CO2 was achieved which is 27.7% lower than that of its counterpart (MEA). The enhanced MDEA/PZ-based technology leads to a low net power efficiency penalty of 7.66% which is 16.1% less than that of the benchmark MEA-based technology. This improvement corresponds to an absolute increase of 1.47% in net efficiency of a 650 MW power plant with PCC units.